Ультрафильтры и разбиения абелевых групп - Протасов, И.В. (Український математичний журнал, 2001)
Доведено, що кожен PS -ультрафільтр на групі без елементів порядку 2 рамсеїв. Для довільного PS-ультрафільтра ϕ на зліченній групі G побудовано відображення f: G → ω таке, що f(ϕ) — P-точка у просторі ω*. Визначено новий клас субселективних ультрафільтрів, значно ширший за клас PS-ультрафільтрів. We prove that every PS-ultrafilter on a group without second-order elements is a Ramsey ultrafilter. For an arbitrary PS-ultrafilter ϕ on a countable group G, we construct a mapping f: G → ω such that f(ϕ) is a P-point in the space ω*. We determine a new class of subselective ultrafilters, which is considerably wider than the class of PS-ultrafilters.